Article 12 and judicial review of administrative action: an analysis. Issue 1 (2nd January 2018) - Sabhapandit, Santanu
ABSTRACT: The centrality of the objective of protecting fundamental rights to judicial review in India is self-evident from Article 32 and Article 226 of the Constitution. Article 12 defines "State" and since fundamental rights are normally enforceable only against the "State", it acts as the broad criterion for amenability to judicial review. The judiciary's approach towards Article 12 has had a lasting effect on how amenability criteria for judicial review are perceived in India. Under Article 226, judicial review may also be conducted for purposes other than the protection of fundamental rights. However, the purpose and scope of, as well as the amenability criteria for such type of judicial review remain unclear. This article demonstrates that a peremptory effect of Article 12 diverts focus from the context of determining amenability and prevents proper engagement with a sphere of judicial review, whose purpose is broader and independent of the purpose of protecting fundamental rights.